Sarawak Foundation / Mohd Adib Suhaimi - Suhaimi, Mohd Adib (Universiti Teknologi MARA, Sarawak, 2015)
Sarawak Foundation was established on May 27th 1971 by the Sarawak State Government under the leadership of YAB Datuk Patinggi Haji Abdul Rahman Ya’kub, which was the Chief Minister of Sarawak at that time. Its first office was located at Jalan Pending, which is formerly the building for the brigade training centre for youth development. The second office or building for the organization was located at Jalan Tun Abang Haji Openg. The building before that was known as Rock Court Flat, which is the living area for high position officer that consists of the English government officers. In April 1973, the building was passed to Sarawak Foundation by the mixed government of Sarawak of that time. Then, in on 15th September 1976, the office of Sarawak Foundation move to Government Secretariat building and the building was fully passed to the organization on 23rd November the same year, and was located at Jalan Masjid Kuching. 13 years later, which is on 1989, Wisma Satok has placed the main office of Sarawak Foundation until March, in the year 2010.